Legionella infections : a review of the literature and a prospective serological study of the incidence of Legionnaires disease at Groote Schuur Hospital - De Goveia, C (Division of Medical Microbiology, 2017)
A prospective study of patients with pneumonia admitted to Groote Schuur Hospital took place over a one-year period in an attempt to assess the incidence of legionella pneumonia. Acute and convalescent serum samples were obtained from 113 patients. Eight patients (7,1%) showed a fourfold rise in antibody titre against Legionella pneumophila group 1 antigen by indirect immunofluorescent test (IFAT). The findings suggest that legionella pneumonia, although not common, should be considered in the aetiology of pneumonia at Groote Schuur Hospital. The results are presented and a review of the literature is undertaken.